The psychology of learning and motivation : advances in research and theory. - Ross, Brian H. (Psychology of learning and motivation ;, 2002)
The Psychology of Learning and Motivation publishes empirical and theoretical contributions in cognitive and experimental psychology, ranging from classical and instrumental conditioning to complex learning and problem solving. Each chapter provides a thoughtful integration of a body of work. Volume 41 includes in its coverage chapters on multimedia learning, brain imaging, and memory, among others.